ANTIBACTERIA ACTIVITY ETHANOL EXTRACT OF ACHRAS ZAPOTA L. FRUIT AND LAGENARIA SICERARIA (MOLINA) STANDL. AGAINST SALMONELLA TYPHI - Saldi Hapiwaty; Yuri Pratiwi Utami; Imrawati; Mahfuzun Bone; Nurjannah Bachri; Rahmah Mustarin; Ainun Jariah; Zahira Amody; Benedikta Winne Angela (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
The Synergistic of antibacterial is an interaction of two antibacterial agents that produces a greater inhibitory effect on bacteria, compared to the individual antibacterial effects of the two agents. The purpose of this study was to determine the synergistic effect of anti-bacterial extract of sapodilla fruit (Achras zapota L.) and water gourd (Lagenaria siceraria (Molina) Standl.) extract against Salmonella typhi bacteria. Extraction of sapodilla fruit and water gourd fruit was carried out by maceration method using 96% ethanol (1:10). Determination of the value of the minimum inhibitory concentration (MIC) of anti-bacterial sapodilla manila fruit and water gourd fruit was carried out by the checkerboard assay method using a 96 wells microplate by calculating the Fractional Inhibition Concentration Index (FICI) value. The results showed that the single MIC value of sapodilla manila fruit and water gourd fruit respectively are 50 mg/mL and 100 mg/mL. The interaction between the two is expressed as a Fractional Inhibitory Concentration Index (FICI) with a value of 1.5. The FICI values ​​indicate different antibacterial effects of the combination of sapodilla fruit and water gourd fruit against Salmonella typhi. Keywords: Synergistic, Salmonella typhi, Achras zapota L., Lagenaria siceraria (Molina) Standl., FICI